Complicações perinatais no Hospital Universitário Cassiano Antonio de Moraes : uma questão de idade? - Almeida, Leonardo Goltara (2013)
The Brazilian population is undergoing a demographic and epidemiological transition, characterized by an increase in life expectancy, declines in mortality rates, birth and fertility, increase education, reduce unemployment, increase in chronic-degenerative diseases and reduction of infectious diseases. Such transitions have also affecting perinatology, with absolute and proportional increase of late pregnancies both in Espírito Santo and in Brazil. This study was a retrospective analysis of pregnancies late in HUCAM comparing those pregnancies with the pregnancies of adolescent and young adult women for the following perinatal outcomes: fetal anomaly, hypoxia in the first and fifth minute, length of gestation, birth weight and type of delivery. The variables were analyzed by categories, and compared by bivariate analysis, using the Fisher's Exact Test, and logistic regression. In the bivariate analysis, we found only an association between maternal age and mode of delivery, but this association was not confirmed in the logistic regression. Analyzing other factors related to pregnancy, remained evidenced a positive association between a lower number of antenatal visits and a higher frequency of hypoxia in the newborn and prematurity (odds ratio 2.9 and 5.7, respectively). At the end of this work are drawn up proposals to improve the collection and storage of data about pregnancy in HUCAM, and to improve prenatal care, aiming at better perinatal outcomes.